The impact of cognitive reserve on delayed neurocognitive recovery after major non-cardiac surgery: an exploratory substudy - Kainz, Elena; Juilfs, Neelke; Harler, Ulrich; Kahl, Ursula; Mewes, Caspar; Zöllner, Christian; Fischer, Marlene (Frontiers in Aging Neuroscience, 2023)
Introduction Delayed neurocognitive recovery is a common and severe complication after surgery and anesthesia with an adverse impact on daily living, morbidity, and mortality. High cognitive reserve may mitigate the development of delayed neurocognitive recovery, however, supporting data is lacking. We aimed to assess the association between cognitive reserve and delayed neurocognitive recovery in the early postoperative period. Methods This is a substudy of two prospective observational studies. Adult patients undergoing elective major non-cardiac surgery, who were fluent in German, were eligible for study participation. Patients with any pre-existing central nervous system disorders were excluded. Cognitive reserve was assessed using the Cognitive Reserve Index questionnaire. Delayed neurocognitive recovery was defined as a decline in cognitive function compared with baseline assessments and was evaluated with a battery of neuropsychological tests on the day of hospital admission and between day three post procedure and before hospital discharge. Results A total of 67 patients with a median age of 67 [IQR: (63–73)] years were included in our analysis. We found delayed neurocognitive recovery in 22.4% of patients. There was a significant association between Cognitive Reserve Index questionnaire total score and the occurrence of delayed neurocognitive recovery in the early postoperative period [OR = 0.938, (95% CI, 0.891; 0.988), p = 0.015]. Conclusion Higher cognitive reserve in elderly patients undergoing major non-cardiac surgery decreases the risk for subsequent delayed neurocognitive recovery in the early postoperative period.